Staff Personnel Management of Principals as a Predictor of Classroom Practices of Teachers in Secondary Schools: Implication for Early Childhood Development - Chukwujiekwu Agbo, Denis; Sunday Ezema, Victor; Kenechukwu Ejionueme, Lambert (International Journal of Psychosocial Rehabilitation, 2021)
This study sought the predictive power of staff personnel management of principals on classroom practices of teachers in secondary schools in South East, Nigeria. A correlational survey research design was adopted for the study using a sample of 794 teachers. Staff Personnel Management Questionnaire and Classroom Practices Questionnaire were used for data collection. The items of the instruments demonstrated good internal consistency reliability indices of 0.89 and 0.75 respectively. The estimates were obtained through a trial testing using Cronbach alpha method. Data collected were analysed using simple regression analysis to answer the research question and the corresponding hypothesis. The finding of the study revealed that staff personnel management of principals had significant (p< .05) positive prediction of classroom practices of teachers. This finding implicates early childhood development in that when the staff personnel management of the preschool headteachers is effective, the preschool teachers will better cater for the development of the children. Based on the findings the researchers recommended that principals should be exposed to management training and retraining programme to enable them acquire the knowledge and skills necessary for their effective functioning; principals should be appointed based not only on qualification and experience but also on management acumen of individuals, and that Federal and State Ministries of Education should redesign staff personnel management and instructional leadership training of principals to emphasize what they mean and not what the individual thinks